Identification of rice Allene Oxide Cyclase mutants and the function of jasmonate for defence against Magnaporthe oryzae. (4th March 2013) - Riemann, Michael; Haga, Ken; Shimizu, Takafumi; Okada, Kazunori; Ando, Sugihiro; Mochizuki, Susumu; Nishizawa, Yoko; Yamanouchi, Utako; Nick, Peter; Yano, Masahiro; Minami, Eiichi; Takano, Makoto; et al.
Summary: Two photomorphogenic mutants of rice, coleoptile photomorphogenesis 2 ( cpm2 ) and hebiba, were found to be defective in the gene encoding allene oxide cyclase ( OsAOC ) by map‐based cloning and complementation assays. Examination of the enzymatic activity of recombinant GST–OsAOC indicated that OsAOC is a functional enzyme that is involved in the biosynthesis of jasmonic acid and related compounds. The level of jasmonate was extremely low in both mutants, in agreement with the fact that rice has only one gene encoding allene oxide cyclase. Several flower‐related mutant phenotypes were observed, including morphological abnormalities of the flower and early flowering. We used these mutants to investigate the function of jasmonate in the defence response to the blast fungus Magnaporthe oryzae . Inoculation assays with fungal spores revealed that both mutants are more susceptible than wild‐type to an incompatible strain of M. oryzae, in such a way that hyphal growth was enhanced in mutant tissues. The level of jasmonate isoleucine, a bioactive form of jasmonate, increased in response to blast infection. Furthermore, blast‐induced accumulation of phytoalexins, especially that of the flavonoid sakuranetin, was found to be severely impaired in cpm2 and hebiba . Together, the present study demonstrates that, in rice, jasmonate mediates the defence response against blast fungus.